A Cross-Sectional Study to Assess the Predictors of Quality of Life in Patients with End Stage Renal Disease in a Tertiary Care Hospital Multan - Bashir, Shaista; Rasool, Muhammad F; Imran, Imran; Sial, Sarfraz H; Majeed, Abdul (Journal of Research (Science), 2025)
Introduction: Globally chronic kidney disease (CKD) has a severe impact on patients health-related quality of life (HRQoL). Hemodialysis (HD) significantly influence HRQoL. Objective: This cross-sectional study was conducted to find out physical, mental and societal factors that affect the quality of life (QOL) with ESRD disease. Methods: The Kidney Disease of Quality of Life (KDQOLTM-36) short form questionnaire was used to measure QOL. Descriptive statistics were used to analyze the individual responses and Pearson correlation, Chi-square tests were utilized to describe the relationship between various patient-specific factors and their QOL. Results: A total of 218 patients (123 male and 95 female) undergoing HD with a mean ± SD of age 40.81 ± 7.42 in years were included in the final analysis. Major cause of ESRD was hypertension (24.8%), followed by diabetes (17%). The mean scores for physical component survey (PCS), mental component survey (MCS) and kidney disease component survey (KDCS) were 23.54 ± 12.69, 28.92 ± 12.86 and 45.01 ± 3.44 respectively. The burden of kidney disease (BKD) had the lowest mean score of 9.90 ± 7.51 and social interaction (58.48 ± 18.19) had the highest mean score. Conclusion: The findings indicate negative effects of the disease on QOL can be observed in dialysis patients. There is a need for more effort towards raising awareness among patients with ESRD about their disease while on treatment. This is important to help control and prevent the disease.